2014
DOI: 10.1007/s00114-014-1204-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior of the male parent predicts brood sex ratio in a songbird

Abstract: Brood sex ratio is often affected by parental or environmental quality, presumably in an adaptive manner that is the sex that confers higher fitness benefits to the mother is overproduced. So far, studies on the role of parental quality have focused on parental morphology and attractiveness. However, another aspect, the partner's behavioral characteristics, may also be expected to play a role in brood sex ratio adjustment. To test this hypothesis, we investigated whether the proportion of sons in the brood is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Indeed, a recent study of our population found that females overproduced the less demanding sex of offspring when mated to large‐patched males (Szász et al . ). Males with larger wing patches feed females less during incubation, which may cause the females to incubate less effectively due to a nutritional constraint (Royama ).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, a recent study of our population found that females overproduced the less demanding sex of offspring when mated to large‐patched males (Szász et al . ). Males with larger wing patches feed females less during incubation, which may cause the females to incubate less effectively due to a nutritional constraint (Royama ).…”
Section: Discussionmentioning
confidence: 97%
“…A link between courtship and parental behaviour of males is also suggested indirectly by several empirical studies that found behavioural traits to play roles in mate choice (Otter and Ratcliffe 1996;Ophir and Galef 2003;Ophir et al 2005;Kunc et al 2006), differential allocation (Gwinner and Schwabl 2005;Grenna et al 2014) or sex allocation (Ramsay et al 2003;Szász et al 2014).…”
Section: Communicated By K Van Oersmentioning
confidence: 81%
“…In a Hungarian population of the species, none of the measured phenotypic traits of the male parent was related to brood sex ratio, but broods became more male-biased as the breeding season progressed (Rosivall et al 2004). Another study in this population, found a reverse seasonal pattern, and revealed that certain phenotypic traits (territorial aggressiveness and body size) of the male parent were also related to brood sex ratio (Szász et al 2014). Finally, in a Czech collared flycatcher population, the proportion of sons in the brood was positively correlated with the investment capacity of the parents and the size of the white wing patch of the male (Bowers et al 2013).…”
Section: Introductionmentioning
confidence: 83%
“…correlative studies on wild songbird populations). The database of the most recent meta-analysis (Booksmythe et al 2015) included all but four studies from our database (Poláková et al 2012, Szász et al 2014, Romano et al 2015, Bonderud et al 2016.…”
Section: Literature Searchmentioning
confidence: 99%